2019
DOI: 10.31125/hunhemsire.630804
|View full text |Cite
|
Sign up to set email alerts
|

Vardiyalı ve Gündüz Çalışan Sağlık Çalışanlarında Uyku Kalitesi, Reaksiyon Zamanı, Stres ve İyilik Halinin Karşılaştırılması

Abstract: Bu çalışma, gündüz ve gece vardiyalı çalışan sağlık çalışanlarının uyku kalitesi, reaksiyon hızı, stres ve iyilik hallerinin karşılaştırmak amacı ile yapılmıştır. Gereç ve Yöntem: Tanımlayıcı nitelikte olan bu çalışmanın katılımcıları, beş farklı kamu ve üniversite hastanesinde çalışan 77 gönüllü sağlık profesyoneliydi (doktor, hemşire, sağlık teknisyeni). Katılımcılar, vardiyalı çalışanlar (24 saat nöbet 24 saat dinlenme) ve gündüz, tam zamanlı (haftada 40 saat) çalışanlar olarak iki gruba ayrılmıştır. Verile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In addition, being a nurse supervisor, and having a bachelor's degree in nursing were found to be factors increasing exposure to "Patient / Visitor incivility". Previous studies have indicated that working nights increases the stress on the individual through sleep deprivation, fatigue and a worsening of the work-life balance (Bumin et al, 2019). As a result, nurses working only night shifts might be more sensitive to incivility.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, being a nurse supervisor, and having a bachelor's degree in nursing were found to be factors increasing exposure to "Patient / Visitor incivility". Previous studies have indicated that working nights increases the stress on the individual through sleep deprivation, fatigue and a worsening of the work-life balance (Bumin et al, 2019). As a result, nurses working only night shifts might be more sensitive to incivility.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Intensive care unit (ICU) nurses have the potential to experience more physical and emotional challenges due to exposure to patient instability, the need to make rapid decisions and actions, high workloads, shift work, long shifts and constant one-to-one patient care. [8][9][10] These factors could increase occupational fatigue among intensive care nurses. [8][9][10] Most occupational fatigue recovery occurs during the non-work period between work shifts.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] These factors could increase occupational fatigue among intensive care nurses. [8][9][10] Most occupational fatigue recovery occurs during the non-work period between work shifts. 11,12 Nurses who are fully rested and functionally alert at the beginning of a work shift may indicate their adaptive recovery level from fatigue acquired during the previous shift.…”
Section: Introductionmentioning
confidence: 99%